Hobby robots - Nargi, Lela (Mankato, MN Amicus Learning, an imprint of Amicus, 2024)
"Questions and answers give kids an understanding about the technology of hobby robots, including robots built for competitions and robots built just for fun. Includes infographics to support visual learning and back matter to support research skills, plus a glossary and index"--
Includes bibliographical references and index.
Ages 5-9
Grades 2-3
112977
Keywords: Robots -- Juvenile literature; Robotics -- Juvenile literature; Juvenile works